Penerapan Teknik Motion Graphics Pada Video Edukasi Bahaya HIV/AIDS di Puskesmas Hulu Gurung - Kurniawan, Heri; Fauzi, Moch Farid (JOURNAL OF APPLIED MULTIMEDIA AND NETWORKING, 2024)
Efforts to prevent the spread of HIV/AIDS require effective education to the public. One innovative approach to conveying information involves the role of technology and interactive media, such as animation, to improve instruction quality. One of the challenges faced by the Hulu Gurung Community Health Center is increasing public awareness about the prevention and dangers of HIV/AIDS. Conventional extension methods, such as lectures and brochures, are starting to receive less attention from the public. 2D animated videos use motion graphic techniques by applying pre-production, production, and post-production design methods. The research data collection used interviews and direct observation methods at the Hulu Gurung Community Health Center. The results of this video were tested using a questionnaire with testing based on the information and multimedia elements used. The results of the questionnaire are calculated using a Likert Scale. The results of this educational video were implemented on the social media platforms Instagram and YouTube. This research can increase knowledge about making animated videos using motion graphic techniques.